(untitled) (Economic and Political Thought, 2022)
The aim of the article is to examine the approach of young studying Poles to cryptocurrencies as a method of payment. The following research hypothesis was put forward: young students have a positive attitude to cryptocurrenceis as a method of payment. To verify the hypothesis we reviewed the Polish and foreing literature, as well as the documents issued by the European Central Bank, European Banking Authority or the European Parliament. Moreover we conducted own research – we prepared the survey and address it to Polish students. The research confirmed the hypothesis, as cryptoassets seem to be a perspective method of payments, and studying Poles have a positive attitude to that currency as a method of payment.